Identifiying role of immune dysregulation in mite-induced allergic rhinits among Malays - Amini, Peyman (2012)
Allergic Rhinitis, the chronic allergic inflammation of nasal mucosa is associated with decreased learning, performance and productivity at work and school, as well as a reduced quality of life. Allergic Rhinitis is a major problem in Malaysia with up to 15% of the adult population affected by this disease. The most common causes for allergic rhinitis in Malaysia are house dust mites, cat fur, dog hair, moulds and cockroach. Established treatment protocols are available for allergic rhinitis. These protocols are mostly based on severity of the disease. However, selection of a proper therapeutic protocol for the patients is not straightforward and as widely acknowledged, the personal burden of illness as experienced by the allergic rhinitis patients cannot be fully assessed by standard clinical symptoms and signs which only moderately correlate with patients' perceptions. Allergy and asthma are inflammatory diseases, caused by dysregulated immune responses in the respiratory mucosa. Although it is clear that Th2-driven immune responses critically effect the development of allergies, the role of upstream immunological regulatory mechanisms (e.g regulatory T cell activity) that develop in vivo to prevent Th2-driven inflammation and prevent allergic symptoms from developing in non-allergic individuals are not clear. This study aims to elucidate the involvement of two main mechanisms in immunology that controls allergic rhinitis: i) diversity in HLA class II genes and the expression of the corresponding T cell receptor V beta gene in regulatory T and effector T-cell populations and ii) the phenotype of the regulating T cell populations important in preventing the symptoms, by comparing with normal individuals. These parameters were also tested as potential markers to predict disease severity. One hundred and sixty four allergic rhinitis patients confIrmed by using relevant clinical criteria and skin prick test were recruited into the study. A semi-assisted questionnaire was used to quantitatively evaluate the severity of the symptoms in patients. From the above, 57 adult Malays with mite-induced AR were further tested using laboratory experiments. Sixty healthy non-allergic individuals from the same ethnic background were also entered into the study as control group. Serum from blood samples was also collected to determine serum total and allergen (mite) specific IgE concentration. Flow cytometric immunophenotyping of PBMCs was performed to determine the expression of cell markers and cytokines associated with regulatory T cells (before and after culture and after specific stimulation with purifIed mite allergen). SpecifIc T -effector (the main contributing T cell type in pathology of allergic diseases) and the total regulatory T cell population (which prevent symptoms and are higher in healthy individuals) were iso lated from the cultured cells using a F ACS sorter. Sorted samples were semi-quantified for the expression of TCR-V~ gene segments using RT-PCR method. MHC class II polymorphism was determined using polymerase chain reaction¬sequence specific primer (PCR-SSP) method. All results were analyzed using statistical analysis software. Demographic and severity-related data derived from questionnaire showed that approximately 60% of allergic rhinitis patients can be classified as "moderate" sufferers. The results from in vivo (prick test) and in vitro (serum IgE) diagnostic methods did not show a significant correlation with symptom severity. Serum levels of specific IgE for Dermatophagoides farina and to a lesser extent, Blomia tropicalis showed positive associations with size of wheal in skin prick test. Polysensitive state of the disease to the mentioned 3 mite species was not a contributing parameter for having a more severe clinical profile. Other disease-specific data which were collected by using the questionnaire (e.g. the concurrent presence of other types of allergy or previous history of allergy) were also not correlated to the disease severity. HLA typing showed that DR7 may have a protective role against mite-induced allergic rhinitis in Malays; while 2.6% of allergic rhinitis patients expressed this allele, its frequency in control group was 14.2% (p-value=0.003). Also from 24 TCR - V~ alleles studied, the expression of V~ 18 on unstimulated effector T cells was significantly higher in allergic rhinitis (p-value=O.O 15) patients. Allergen-specific stimulation caused this prominent allele to shift to V~7 (p-value=0.006).